2019
DOI: 10.1063/1.5064454
|View full text |Cite
|
Sign up to set email alerts
|

Polarization controlled photovoltaic and self-powered photodetector characteristics in Pb-free ferroelectric thin film

Abstract: Ferroelectrics are considered next generation photovoltaic (PV) materials. In this work, a switchable and large PV effect is demonstrated in a Pb-free ferroelectric 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 (BZT-BCT) thin film fabricated by a pulsed laser deposition technique. The material shows a remarkable PV output of 0.81 V due to its morphotropic phase boundary composition. The observed PV effect is analyzed on the basis of the interfacial Schottky barrier and bulk depolarization field. The poling dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Figure 5A-E shows the specific detectivities (D*) of the PDs with various Ti contents at different poling voltages. D* reflects the ability of the device to detect weak light signals from noise and can be expressed as Equations (4): 17 As seen from the figures, when the Ti content improves from 40 mol% to 80 mol%, the D* increases to the value of 5.45 × 10 10 Jones at a poling voltage of 2 V, which results from the increase in R λ . However, by further increasing the Ti content, the PDs with 87.5 mol% Ti exhibit a D* value of only 0.89 × 10 10 Jones at the same poling voltage, although it has the largest R λ of 4.17 mA/W, which is attributed to its high dark current (1700 pA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5A-E shows the specific detectivities (D*) of the PDs with various Ti contents at different poling voltages. D* reflects the ability of the device to detect weak light signals from noise and can be expressed as Equations (4): 17 As seen from the figures, when the Ti content improves from 40 mol% to 80 mol%, the D* increases to the value of 5.45 × 10 10 Jones at a poling voltage of 2 V, which results from the increase in R λ . However, by further increasing the Ti content, the PDs with 87.5 mol% Ti exhibit a D* value of only 0.89 × 10 10 Jones at the same poling voltage, although it has the largest R λ of 4.17 mA/W, which is attributed to its high dark current (1700 pA).…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Thus, self-powered UV PDs based on ferroelectric materials have recently attracted increasing interest. 17,18 In recent work, we have confirmed that La-doped Pb(Zr,Ti)O 3 thin film is a promising material for preparing ferroelectric photovoltaic devices due to its high remnant polarization, resulting in efficient separation of the photogenerated electrons and holes. 19,20 This material may render self-powered UV PDs with high photoelectric response performances.…”
Section: Introductionmentioning
confidence: 81%
“…The specific detectivity D* presents the ability to detect weak light source signals and reflects the noise in the environment, that is, D* = R/(2e·I d /S) 1/2 , [30] where I d is the value of current in the dark. [9,26] Here, we also demonstrate the value of the largest output powers in Ag/BFO/ITO photodetector by loading different resistances under 365 nm illumination (105.2 mW cm −2 ) at three typical temperatures. The above results indicate that the Ag/BFO/ITO photodetector applies to detect at temperature range around 66.1 °C.…”
Section: Resultsmentioning
confidence: 58%
“…This may be caused by the temperature-modulated bandgap and barrier height in Ag/BFO/ITO device. [23][24][25][26] As compared with the conventional battery-powered counterparts, the self-powered photodetectors provide advantages of long lifespan and easy integration. above mentioned solar cells, ferroelectric materials, which can exhibit abnormal photovoltaic effect evidencing by above bandgap photovoltage, have attracted much attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation